Vloga mednarodnih razvojnih strategij pri oblikovanju regionalnih razvojnih strategij - Saunavaara, Juha (Urbani izziv, 2017)
During the past decades, national governments and international institutions have both searched for ways to equalise disparities and revitalise lagging regions. Although ideas and examples of the most effective ways to achieve these goals originate in various places, their influence is inclined to permeate elsewhere. Therefore, the processes involved in policy transfers are highly relevant from the perspective of regional development. This study approaches these processes through the case study of post-war Hokkaido and pays special attention to the role of three international development strategies: the Tennessee Valley Authority model, the Growth Pole Theory and the Industrial Cluster Theory. As a result, this research shows the wide variety of agents involved in policy transfer, analyses the processes of incorporating exogenous ideas into regional development polices and demonstrates the variety of sources from which different agents can draw lessons.
Keywords: Hokaido; Japonska; razvojna strategija; regionalna politika; regionalni razvoj; regionalno planiranje